Intelligent life in the universe :principles and requirements behind its emergence - Ulmschneider, Peter (Berlin, Springer-Varlag, 2006)
Intelligent Life in the Universe: Principles and Requirements Behind Its Emergence (Advances in Astrobiology and Bio geophysics)
Keywords: Astrobiology; Biogeophysics; Mathematics